Experiences of Using Weighted Blankets among Children with ADHD and Sleeping Difficulties - Maria Lönn; Katarina Aili; Petra Svedberg; Jens Nygren; Håkan Jarbin; Ingrid Larsson (Occupational Therapy International)
Introduction. Sleeping difficulties are common in children with attention deficit hyperactivity disorder (ADHD). A sleep intervention with weighted blankets was designed to increase current understanding of using weighted blankets to target children’s individual needs in connection with sleep and daytime functioning. Aim. To explore how children with ADHD and sleeping difficulties experience the use of weighted blankets. Methods. An explorative qualitative design in which 26 children with ADHD and sleeping difficulties, 6–15 years old, were interviewed about a sleep intervention with weighted blankets. Four categories emerged from qualitative content analysis. Results. Children’s experiences revealed that the use of weighted blankets 1) requires a commitment, by adjusting according to needs and preferences and adapting to the environment; 2) improves emotional regulation by feeling calm and feeling safe; 3) changes sleeping patterns by creating new routines for sleep and improving sleep quality; and 4) promotes everyday participation by promoting daily function and balancing activity and sleep. Conclusions. Using weighted blankets promoted children’s management of daily life with ADHD and sleeping difficulties. Occupational therapists can improve the assessment and delivery of weighted blankets tailored to individual needs based on increased knowledge from the children themselves.